Study of E-Waste Management and Indian Scenario - Daya Shankar Singh (International Journal of Scientific Research in Science and Technology, 2025)
India is the world's third-largest generator of e-waste, producing millions of tonnes annually. This paper analyzes the dual structure of India’s e-waste recycling, contrasting the regulated, under-resourced formal sector with the efficient but hazardous informal sector. It examines the serious environmental and public health consequences stemming from informal recycling methods, such as soil and water contamination from heavy metals. Furthermore, it discusses the evolution of India's e-waste policies, including the crucial Extended Producer Responsibility (EPR) regulations, and highlights the economic opportunities presented by "urban mining" to recover valuable materials. The paper concludes with strategic recommendations for fostering a sustainable, equitable, and efficient e-waste management system in India.
Keywords: EPR; E-Waste; Crude Method